Dynamic Impact of Energy Consumption on the Growth of Nigeria Economy (1986-2016): Evidence from Symmetrical Autoregressive Distributed Lag Model - Comfort, Egbichi; Ojamaliya, Abuh; Victoria, Okafor; Abigail, Godwin; Oluwapelumi, Adedoyin (International Journal of Energy Economics and Policy, 2018)
This paper empirically examined the dynamic impact of energy consumption on the growth of Nigeria economy between 1986 and 2016 using symmetrical ARDL model approach. Findings from the study revealed that electricity consumption has not had a significant impact on the growth of the Nigerian economy. It shows that due to fluctuations in electricity supply, the growth of Nigerian economy has been on the decline. However, petroleum consumption was discovered to have a significant impact on economic growth in Nigeria; while gas consumption was discovered to have no significant impact on the growth of Nigeria economy. This was attributed to gas flaring activities and other environmental abuses that had caused major Niger-delta crisis and attendant consequences like pipeline vandalization and hostage taking. Suggestive from the study therefore are that government should undertake a cogent approach towards reforming the electricity supply sector as its paramount for the country’s quest for industrialization. Keywords: Energy consumption, Economic Growth, Petroleum, Gas and Electricity JEL Classifications: O13, P28, O44